A Study of Factors Influencing the Enzymatic Elimination of Adenosine Diphosphate in Blood - Howe, E. E; Bosshardt, D. K (Thrombosis and Haemostasis, 1968)
The red cells carry by far the greater part of the enzyme systems capable of eliminating adenosine diphosphate found in the blood but this activity is more concentrated in the platelets.These “ADPase” systems are strikingly stimulated by divalent cations with Mg++ being the most effective ion. Ca++, while possessing some effect, is antagonistic to Mg++ in the platelet system.A heat stable enhancing factor for the platelet “ADPase” system was shown to be present in platelet poor plasma. This factor was ineffective in preparations obtained from erythrocytes.